Inovasi Bahan Ajar Pendidikan IPS Berbasis Digital Flipbook Terintegrasi Local Wisdom Dalam Menunjang Perkuliahan Jarak Jauh - Piki Setri Pernantah; Mifta Rizka; Ciptro Handrianto; Een Syaputra (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2022)
The problem of distance lectures is quite a lot, it is expected to encourage the development of digital flipbook-based teaching books so that they can be accessed easily and quickly by students who can help smooth lecture activities, especially in social studies learning. Another important reason, this digital flipbook-based textbook was developed: first, there is no social studies textbook integrated with local wisdom; second, the absence of learning materials based on digital flipbooks that have been used in previous online and offline learning; third, the lack of values education based on Malay local wisdom in social studies learning. The model used in this development research is a 4D model from (Four D Models) according to Thiagarajan. This development model was chosen because it aims to produce products in the form of social studies learning materials based on digital flipbooks integrated with local wisdom.